1985
DOI: 10.1159/000242162
|View full text |Cite
|
Sign up to set email alerts
|

Placental Handling of Zinc in the Guinea Pig

Abstract: The distribution of zinc between the mother and the fetoplacental unit, and its placental transfer, were studied using stable and isotopic zinc in unanaesthetized pregnant guinea pigs and an in situ perfusion preparation. The concentration of stable zinc in fetal plasma and skeletal muscle was higher than that in the maternal tissues: 2.0 compared with 1.4 μg/ml and 84 with 49 ng/mg dry weight, respectively. The placenta and maternal and fetal liver had similar zinc concentrations: 90, 75 and 88 ng/mg dry weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 13 publications
3
10
0
Order By: Relevance
“…This could arise if the binding proteins in the tissue take up or release zinc by mass action. This conclusion is in agreement with Simmer et al 1985).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This could arise if the binding proteins in the tissue take up or release zinc by mass action. This conclusion is in agreement with Simmer et al 1985).…”
Section: Discussionsupporting
confidence: 93%
“…The maternal aspect of the placenta could be the principal barrier to materno-fetal transport of zinc. In studies on the guinea-pig such transfer occurred against a concentration gradient and when placental zinc levels exceeded those in fetal and maternal plasma (Simmer et al 1985). The maternal surface appeared to be rate controlling and it was concluded that zinc is taken up by active transport at the maternal surface of the placenta and released across the fetal surface by diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…The positive correlation found in our study and by others [6,7] between maternal and cord values of serum zinc, and particularly the higher cord serum zinc that we observed in women with serum zinc in the higher quartile, are consistent with findings in the guinea pig [21], In this animal species, maternal-fetal mass transfer of zinc was directly related to maternal plasma zinc concentrations, being non-saturable even in the upper range of physiological levels. This could be due to a more favorable diffusional placental-fetal gra dient of zinc with increasing maternal circu lating zinc concentrations.…”
Section: Effect O F Maternal Serum Zinc Levelssupporting
confidence: 93%
“…particularly in humans. Transfer seems to depend both on maternal and fetal serum zinc-binding ligands [4], with differences in affinity and concentrations possibly playing a role, as has been in part demonstrated in the guinea pig [21,22], Transfer may also depend on placental uptake, utilization and release to the fetus, related to membrane transport sys tems in the svncytiotrophoblast [23], placen tal zinc-binding proteins [24,25] and placen tal metabolism [26].…”
Section: Effect O F Maternal Serum Zinc Levelsmentioning
confidence: 90%
See 1 more Smart Citation